PET-CT Beyond FDG A Quick Guide to Image Interpretation - Fanti, Stefano; Farsad, Mohsen; Mansi, Luigi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Although [18F]fluorodeoxyglucose (FDG) generally shows an excellent performance as a cancer-imaging agent when using PET-CT, there are some settings in which other radiopharmaceuticals offer advantages. Such non-FDG tracers are now gaining widespread acceptance not only in research but also in clinical practice, with the acquisition of promising results in the management of various cancers. This atlas, including about 500 high-quality images, is a user-friendly guide to PET-CT imaging beyond FDG. A wide range of tracers is covered, such as 18F- and 11C-choline, 11C-methionine, 18F-ethyl-L-tyrosine, 68Ga-DOTA-NOC, 11C-acetate, 11C-thymidine, and 18F-DOPA. Throughout, the emphasis is on image interpretation, with guidance on the recognition of normal, benign, and malignant uptake and clear instruction on learning points and pitfalls. This book is a companion to the editors$1 (Brecently published Atlas of PET-CT, which focuses exclusively on the use of FDG. It is designed to serve as a reference text for both nuclear physicians and radiologists, and will also be of great benefit to radiographers, technologists, and nuclear medicine and radiology residents.s
Importance of Radiotracers Other than FDG in Oncology -- Considerations About PET Isotopes -- Choline PET-CT -- Methionine PET-CT -- Fluoride PET-CT -- Tyrosine PET-CT -- Somatostatin Receptor PET-CT -- Acetate PET-CT -- Thymidine PET-CT -- Dopa PET-CT -- Imaging of Hypoxia with PET-CT -- Angiogenesis PET Using Radiolabeled RGD Peptides -- Hormonal Receptors PET-CT -- HTP PET-CT.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Oncology; Medicine & Public Health; Nuclear Medicine; Imaging / Radiology; Oncology